Oncotic (Myxomatous) Aneurysms: A Review of Management - Peres, Carlos Michel Albuquerque; Brito, Alyce Castro de; Peres, Carlos Henrique Mesquita; Reichl, Alfredo Coimbra; Dutra, Laila Patricia Fidelis (Arquivos Brasileiros de Neurocirurgia: Brazilian Neurosurgery, 2022)
Atrial myxomas are the most common primary cardiac tumors and may manifest with neurological symptoms in ∼ 30% of cases. Cerebral ischemia, aneurysmal formation, and extravascular metastases are mechanisms that lead to these neurological manifestations. Perilesional changes on computed tomography (CT) and magnetic resonance imaging (MRI) may help in the diagnosis of myxomatous aneurysms, which are usually located in the distal middle cerebral artery (MCA) and in the posterior cerebral artery (PCA) circulation territories. Careful resection of the cardiac lesion is essential for preventing embolism. However, treatment of myxomatous aneurysms is controversial due to the limited understanding of the natural history of this condition. Treatment may include clinical observation in asymptomatic patients, surgical resection, endovascular approaches, adjuvant chemotherapy, and low-dose radiation therapy. We present one case of a female patient with myxomatous aneurysm secondary to an atrial myxoma who presented with neurological symptoms and another case of a female patient who developed neurological symptoms after initial surgical treatment of the primary lesion. Lesion growth rate, topography, morphology, and the patient's clinical condition must be considered when choosing a therapeutical method. Further clinical studies are needed to achieve a better understanding and treatment of this disease.
Keywords: oncotic aneuryms; myxomatous aneurysm; intracranial aneurysm; fusiform aneurysm; atrial myxoma; embolization